Prostitutes, sailors and professionals - lived experiences of medical school students and staff with tattoos [version 1; peer review: 2 approved] - Kevin McConville; Shubham Agwan (MedEdPublish, 2023)
Background: The aim of this study was to explore the lived experiences of medical school students and staff to uncover gaps in policy and its effects on those with tattoos. Methods: Adopting a phenomenological design, semi-structured interviews were conducted with ten medical teaching staff and students who had tattoos, within one university medical school. Five key themes emerged: tattoo motives, tattoo content, positive and negative views on tattoos and challenges for establishing policy. Results: Findings suggested that no existing stigma towards staff or students exists, however, there is an absence in existing policy regarding tattoos. Participants’ motivations for obtaining tattoos mirrored those of the public, most commonly being artistic expression. Images of tattoos related to nature were common. Views on tattoos suggested the need for a full reform of ‘dress code’ policy for the profession. Several ethically laden scenarios were espoused, highlighting the need for an official stance on tattoos. Policy discussions flagged challenges for those who construct such documents; cultural and generational differences being commonly identified by participants. Conclusions: Universally there was uncertainty on current policy, with no individual able to recount specific guidance. The existence of a hidden curriculum surrounding tattoos within medical school further increases the need for guidance reform.